2009
DOI: 10.1186/1472-6815-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Primary Nasopharyngeal non-Hodgkin lymphomas: a retrospective review of 26 Moroccan patients

Abstract: BackgroundNasopharyngeal non-Hodgkin lymphomas (NNHL) are extremely rare. In this study, we will report the progress achieved in the management of this disease in our institute.MethodsWe retrospectively reviewed the records of 26 patients having primary NNHL who were managed between January 1997 and December 2008, to evaluate and compare their clinical characteristics and treatment outcome. Clinical variables, including age, sex, stage, and treatment modality, were assessed. Disease free survival and overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 19 publications
(28 reference statements)
3
30
1
Order By: Relevance
“…A few studies are reporting the clinical characteristics of NH lymphomas [ 22 , 23 ]. Hsueh et al reported that in 35 cases of NPL during 22 years’ follow-up with the average age of 59.6 years, WBC of 12,992/mm 3 , LDH of 337.7 U/L, and the meantime from initial symptoms to diagnosis of 2.6 months, neck lymph nodes involvement or other distant involvements were detected in less than a third of patients at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies are reporting the clinical characteristics of NH lymphomas [ 22 , 23 ]. Hsueh et al reported that in 35 cases of NPL during 22 years’ follow-up with the average age of 59.6 years, WBC of 12,992/mm 3 , LDH of 337.7 U/L, and the meantime from initial symptoms to diagnosis of 2.6 months, neck lymph nodes involvement or other distant involvements were detected in less than a third of patients at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…NHL of the nasopharyngeal region is usually invasive and has a strikingly poor prognosis than other extranodal lymphomas [ 24 ]. Also, localized disease and low-grade NPL are associated with a better prognosis [ 22 ]. Moreover, B symptoms have been reported to be associated with poor prognosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…). Nasal endoscopic biopsy pathologically confirmed diffuse large B‐cell lymphoma . Our case emphasizes the importance of thorough history‐taking and clinical examination to identify “red flags” in patients with cluster‐like headache.…”
mentioning
confidence: 62%
“…Nasal endoscopic biopsy pathologically confirmed diffuse large B-cell lymphoma. 3,4 Our case emphasizes the importance of thorough history-taking and clinical examination to identify "red flags" in patients with cluster-like headache. Neuroimaging should always be closely reviewed in patients with cluster-like headache to ensure that a secondary headache is not overlooked.…”
mentioning
confidence: 88%
“…Surveillance scans are performed at 6 monthly or yearly intervals, or as clinically indicated and the surveillance policy may vary between institutions. In the head & neck region, the sites commonly infiltrated by lymphoma include Waldeyer's ring, tonsils, nasopharynx and the base of the tongue (Wafa et al 2009). Anatomically, Waldeyer's ring form the opening to the upper aerodigestive tract and is the initial site of contact between the mucosa-associated lymphoid tissue antigens and the inhaled, ingested or exogeneous antigens.…”
Section: Factors Associated With Pet-ct Positivity In the Head And Neckmentioning
confidence: 99%